Comparative Pharmacokinetics of a Single Oral Dose of Two Formulations of Amlodipine - Pico, Jose Carlos; Domínguez, Graciela; Negri, Armando Luis; Caubet, Juan Carlos; Terragno, Norberto Antonio (Arzneimittelforschung, 2008)
Amlodipine, a long acting dihydropyridine calcium channel antagonist, is prescribed worldwide for the treatment of angina and hypertension. The objective of this study was to compare the pharmacokinetics and to establish bioequivalence of two formulations of amlodipine. The study was performed at the Clinical Pharmacology Unit, Hospital de Clínicas, Medical School of Buenos Aires University. This randomized, single blind, two-period, two-sequence, comparative crossover study was conducted in 24 Caucasian healthy volunteers. A single oral 10 mg dose of amlodipine besylate (CAS 111470-99-6) test formulation and reference formulation were administered to the volunteers separated by a 3-week washout period in a crossover manner. Blood samples for pharmacokinetic analysis were collected over a period of 144 h after drug administration. Amlodipine was measured in plasma samples using a validated HPLC method with LC-MS-MS detection. A non-compartmental method was used for pharmacokinetic analysis. Bioequivalence between test and reference amlodipine samples were demonstrated as the calculated 90% confidence interval for the corresponding ratios of log transformed pharmacokinetic parameters (AUCt, AUC∞ and Cmax) fell within the 80–125% range, the predetermined criterion for pharmacokinetic equivalence.
Keywords: Amlodipine besylate, bioequivalence, pharmacokinetics; Calcium channel antagonists, dihydropyridine; CAS 111470-99-6